The Implementation of Prediction Strategy in Increasing Students’ Reading Comprehension in English Recount Text at SMA Negeri 9 Wajo - Muhammad Irham; Geminastiti Sakkir; Nur Aeni (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
The purpose of this study is to improve reading comprehension of English recount texts through predictive strategies in learning English. This study used a quantitative descriptive method. The data from this study were collected from the results of the pre-test and post-test. The subjects of this study were second grade students at the final secondary level consisting of 23 students selected using random sampling with the help of the teacher. The results of the data showed that there was an increase in post-test scores after the Prediction approach was used. This increases with an average score of understanding (32.2%) of the average score in the pre-test, which is 56.9 and the post-test is 84. This shows that the post-test understanding score is higher than the pre-test. The conclusion is predictive strategies are effective for increasing the reading comprehension of class XI students at SMA Negeri 9 Wajo. Therefore, predictive strategies to improve students' reading comprehension skills are very important and useful in the process of teaching and learning English.